Characterising language policy and planning in international organisations: ASEAN insights. Issue 2 (15th March 2022) - Lee, Huan Yik; Hamid, M. Obaidul; Hardy, Ian
ABSTRACT: Although most international organisations are, in principle, multilingual, the ten-member Association of South East Asian Nations (ASEAN) has adopted a radical approach by operating monolingually, ostensibly for convenience and pragmatism. In order to provide an evaluation of the ASEAN policy context, this paper compares and contrasts ASEAN to two other more familiar international organisations, namely the United Nations (UN) and European Union (EU). The paper attempts to rationalise language policy and planning (LPP) in these organisations, grounded in principles such as equality, inclusivity, practicality, instrumentality, economic viability and even arguably, 'neutrality' in the context of ASEAN. These principles are discussed in relation to two underlying models of language ideology, i.e. linguistic pluralism and internationalisation, which characterise ASEAN, EU and UN LPP. The article presents the argument that ASEAN has embraced English-only monolingualism, rooted in internationalisation, while both UN and EU strive to achieve plurilingualism, albeit through divergent multilingual operational models. The analysis, however, shows that the ideology of linguistic pluralism characterising UN and EU is at best symbolic, as this ideology has practically maintained the hegemony of English and, to some extent, the other languages of power. This suggests that ASEAN may not have much to learn from EU or UN for an alternative to its English-only policy.